Active‐Matrix‐Based Flexible Optical Image Sensor. Issue 9 (16th June 2021) - Xuan, Yan; Lu, Yuyao; Honda, Satoko; Arie, Takayuki; Akita, Seiji; Takei, Kuniharu
Abstract: Owing to the demand for the development of Internet of things devices, multiple sensor platforms are of great interest to society and its future electronics. One of these emerging devices is a mechanically flexible sensor system that can attach and conform to nonplanar surfaces, unlike conventional inflexible sensor chips. To realize this concept, a variety of flexible sensor systems must be developed from materials to system integrations. This study proposes a flexible sensor system as one of the candidates: an active‐matrix‐based flexible optical image sensor that uses a stacked nanosheet film formed by a solution process and transistors. The results show that the sensor can be utilized as an optical imager because it detects enough optical stimuli. In addition to the sensitivity, the mechanical flexibility of the active‐matrix optical sensor is tested, and the results exhibit good electrical stability even after 1000 bending cycles and 0.85 cm bending radius. The mapping of light distribution is successfully demonstrated under both flat and curved conditions. This flexible optical sensor array shows the high possibility to image the light distribution for high‐resolution and low power mapping realized by active matrix circuit integration. Abstract : Flexible optical image sensor integrated on active‐matrix circuitry is demonstrated using solution‐based stacked nanosheet layers as an optical sensing material. After confirming the good electrical and mechanical performance of the integrated flexible device, a 13 × 7 array is tested to map light distribution under bending condition as a proof‐of‐concept.